GBA-Associated Synucleinopathies: Prime Candidates for Alpha-Synuclein Targeting Compounds - Brockmann, Kathrin (Frontiers in Cell and Developmental Biology, 2020)
With disease-modifying compounds targeting alpha-synuclein available in clinical trials, patient stratification according to alpha-synuclein-specific enrichment strategies is a much-needed prerequisite. Such a scenario will be exemplified for GBA, one major genetic risk factor that is specifically associated with the alpha-synucleinopathies: Parkinson’s disease and dementia with Lewy bodies.